Answer

Verified

429.3k+ views

**Hint:**We have a given set of equation:

$\begin{align}

& 3x+2y+25=0......(1) \\

& 2x+y+10=0......(2) \\

\end{align}$

To get the values of x and y we need to solve the given set of linear equations. We can solve a set of equations using a substitution method. In the substitution method, we get the value of one variable in terms of another variable from one equation and substitute it in the other equation to get the value of another variable. So, we will rearrange equation 1 and take y in terms of x and substitute it in rearranged equation 2.

**Complete step-by-step solution**

We can write the set of linear equations as:

$\begin{align}

& 3x+2y=-25......(3) \\

& 2x+y=-10......(4) \\

\end{align}$

So, by applying substitution method for the given set of linear equations:

From equation (4), we can write:

$\begin{align}

& 3x+2y=-25 \\

& \Rightarrow 2y=-25-3x \\

& \Rightarrow y=\dfrac{-25-3x}{2}......(5) \\

\end{align}$

Now, we get the value of y in terms of x.

Put the value of y in equation (3), we get:

$\begin{align}

& \Rightarrow 2x+y=-10 \\

& \Rightarrow 2x+\left( \dfrac{-25-3x}{2} \right)=-10 \\

& \Rightarrow 4x-25-3x=-20 \\

& \Rightarrow x=5......(6) \\

\end{align}$

Put the value of x from equation (6) in equation (5) to get the value of y:

So, we have:

\[\begin{align}

& y=\dfrac{-25-3\left( 5 \right)}{2} \\

& =\dfrac{-25-15}{2} \\

& =\dfrac{-40}{2} \\

& =-20

\end{align}\]

**Hence, x = 5 and y = -20**

**Note:**There is another method to solve a given set of linear equations, i.e. Elimination method. In the elimination method, we multiply or divide both the equations with a number to eliminate one variable in both the equations by adding or subtracting them and get the value of another value. Then we put the value in one of the equations and get the value of the eliminated variable.

For the given set of equations:

$\begin{align}

& 3x+2y=-25......(1) \\

& 2x+y=-10......(2) \\

\end{align}$

Multiply equation (1) by 2 and equation (2) by 3, we get:

$\begin{align}

& 6x+4y=-50......(3) \\

& 6x+3y=-30......(4) \\

\end{align}$

Subtract equation (4) from equation (3); we get:

$\begin{align}

& \Rightarrow 4y-3y=-50+30 \\

& \Rightarrow y=-20......(5) \\

\end{align}$

Now put the value of y from equation (5) in any of the above equation to get the value of x.

Let’s put value of y in equation (1), we get:

$\begin{align}

& \Rightarrow 3x+2y=-25 \\

& \Rightarrow 3x+2\left( -20 \right)=-255 \\

& \Rightarrow 3x-40=-25 \\

& \Rightarrow 3x=15 \\

& \Rightarrow x=5 \\

\end{align}$

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE

Which are the Top 10 Largest Countries of the World?

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

How do you graph the function fx 4x class 9 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths